2013
DOI: 10.1097/mib.0b013e31827f27f4
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Helminth Exposure Is Protective Against Inflammatory Bowel Disease

Abstract: This study demonstrates a protective association of childhood helminth infection against the development of IBD and supports the "hygiene hypothesis" that improved living conditions may increase the incidence of IBD. Our epidemiologic conclusions provide support that helminths may have immunomodulatory effects which provides protection against the development of IBD later in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 30 publications
(33 reference statements)
2
32
0
1
Order By: Relevance
“…Research into the anti-inflammatory properties of helminth infection is inspired by the hygiene hypothesis 75 , and the eradication of helminths in the industrialized world, where autoimmune diseases are most prevalent. Indeed, a recent case control study in South Africa found childhood helminth infection to be protective against IBD (adjusted odds ratio = 0.2) 125 . The majority of studies use the porcine whipworm, Trichuris suis , due to its accessibility in large numbers, its ability to temporarily and safely colonize humans, and the lack of transmission between close human contacts 126 .…”
Section: Potential Solutions and Recommendationsmentioning
confidence: 99%
“…Research into the anti-inflammatory properties of helminth infection is inspired by the hygiene hypothesis 75 , and the eradication of helminths in the industrialized world, where autoimmune diseases are most prevalent. Indeed, a recent case control study in South Africa found childhood helminth infection to be protective against IBD (adjusted odds ratio = 0.2) 125 . The majority of studies use the porcine whipworm, Trichuris suis , due to its accessibility in large numbers, its ability to temporarily and safely colonize humans, and the lack of transmission between close human contacts 126 .…”
Section: Potential Solutions and Recommendationsmentioning
confidence: 99%
“…Furthermore, several studies have shown that children in farm environments have less allergic disease compared with those raised in urban environments, including Amish children in northern Indiana [41], children living in Alpine farm environments [42] and an Austrian study that showed there was more hay fever and asthma in children living in city versus farm environments, where a more diverse microbiome is likely to be acquired [43]. In addition, Azad et al utilized a natural experiment to show that microbial diversity increased in the guts of children exposed to pets, which simultaneously resulted in lower levels of atopy and allergic disease relative to children with lower levels of diversity in their gut flora [44], and in another experiment, patients who were inoculated with eggs from Trichuris suis , a flatworm that does not cause disease, saw a significant reduction in Crohn’s disease [45]. The results of this study are additionally supported by an unmatched case-control study in South Africa that showed that helminth infection was protective against both Crohn’s disease and ulcerative colitis [46].…”
Section: Essential Learning Objectivesmentioning
confidence: 99%
“…Our cohort may have included a higher proportion of patients with ‘complicated’ disease as GSH and TBH are both referral based IBD centers. Poor socioeconomic status is associated with helminth infection and in South Africa helminth infection has been shown to be protective against IBD development [62]. Therefore it is entirely possible that within our cohort this may have influenced the severity of CD between the racial groups however this was not one of the variables evaluated in the present study.…”
Section: Discussionmentioning
confidence: 86%